The Perceptions and Acceptance of General Population toward the National Health Insurance Program in Iraq - Sara Asaad Kadhim; Ali Azeez Al-Jumaili; Ehab AbdulKareem Khalaf; Noha H. Helmy; Majd Al-hurr; Bernard Sorofman; William Doucette (Iraqi Journal of Pharmaceutical Sciences, 2025)
The new Iraqi health insurance plan was approved by the Iraqi parliament in 2021 and became a law that should be implemented in the next couple of years. This study is collaboration between the University of Baghdad/ College of Pharmacy and the Health Insurance Authority which is the responsible body for the new health insurance program implementation. The study aimed to measure the general population's awareness and acceptance of the new national health insurance program in order to get over any obstacles that might arise during the implementation process. This study was a cross-sectional study using an electronic survey for the general population. A Google Form was used to distribute the survey via social media platforms. The survey items were adopted with modifications from a previous study to measure general population awareness, perceived benefits, and challenges that may face the implementation. The recruitment of participants took place from February 2023 to September 2023. The study received 562 completed surveys and the majority were female (63.7%). More than half (55.5%) were university students and 24.4% were government employees. The majority were from Baghdad (61.2%). More than half (54.6%) of them were unaware of the details of the new Iraqi health insurance law. More than three-quarters (76.7%) supported and were willing to join the new insurance plan. Most of the participants (68.5%) considered paying 1% of their salary per month to be reasonable. About 71.2 % of them believe that the quality of service would improve in the public sector and create competition with the private one by the implementation of the health insurance law. About 42% of the participants were dissatisfied with the health services in the private sector compared to the cost they paid; on the other hand, 56% were dissatisfied with the current semi-free health services in the public sector. In general, there is positive perception among the general population regarding the new health insurance plan particularly to enhance the quality and overuse of the current healthcare services. Low satisfaction with the current services and the affordability of the new health plan would encourage people to join the program. General populations need more advertising campaigns to be aware of the details of the health insurance program.